Strategi Pemasaran Kreatif untuk UMKM: Memperkuat Daya Saing Toko Riski Jaya Snack - Hotimah, Husnul; Supendi, Moh. (Fakultas Ekonomi Universitas Samudra, 2025)
The aim of this research is to analyze the marketing strategies used to increase the competitiveness of MSMEs, namely the Riski Jaya Snack snack shop. This research uses a descriptive qualitative approach through observation, interviews with sources determined using purposive sampling (i.e.: owners, employees and distributors), and is accompanied by documentation. Data analysis uses data reduction methods, data display and drawing conclusions. The results show that the Riski Jaya Snack store uses three types of marketing strategies, namely market development strategy, product development strategy, and push and pull strategy. These three strategies are supported by good service and products as an effort to increase the competitiveness of the snack shop.